Megan’s Law 20 Years Later: An Empirical Analysis and Policy Review - Zgoba, Kristen (Criminal justice and behavior, 2018)
This present study examines the sexual and general recidivism rates of 547 convicted sex offenders released before and after the enactment of Megan’s Law in New Jersey. Presenting the longest Megan’s Law evaluation, participants were followed for an average of 15 years after release (range = 10-29 years). Bivariate and multivariate logistic regression equations were estimated to identify covariates significantly associated with both sexual and general recidivism. Group-based trajectories of general recidivism within the 10 years post-prison release were also estimated and compared according to pre-Megan’s Law and post-Megan’s Law release status. No differences in recidivism rates were noted between the cohorts, but differences emerged in the offending trajectories of the high-risk group of offenders within 10 years of release. These results highlight the lack of impact that sex offender registration and notification (SORN) laws have on sexual and general reoffending rates postrelease.